Farmers' Intention to Leave The Agricultural Sector in East Java, Indonesia: A Crisis Through Non Agricultural Job Opportunities Challenges - Yuliati, Nuriah -; Dr, Kusnandar; Soedarto, Teguh; Rahayu, Endang Siti (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
Farmers' intention to leave the agricultural sector is a crucial reasoned action for the future of the Indonesian agricultural sector. The aims of research are describe the type of livelihood that sustains the farm household's economy, and analyze the influence of Job Opportunities toward Farmer's Intentions Leaving the Agriculture Sector. The sampling was done by multistage sampling so that 360 households of paddy farmers were obtained in six villages, Bangil sub-district, Pasuruan Regency, Province of East Java. Data analysis using descriptive statistics and Structural Equation Modelling (SEM) PLS analysis with Warp PLS software. The findings of the study indicate that the relatively large number of non-agricultural jobs carried out by the household labor of farmers, most of them are trade and factory employees. The best job opportunity is in line with farmers' favorite choice for non-agricultural livelihoods. Employment opportunities have a positive and significant impact on farmers' intention to leave the agricultural sector.